Change and continuity : statute, equity, and federalism - Gummow, W. M. C. (Oxford : Oxford University Press, 1999)
"This volume is based closely on the lectures delivered by the Hon. Justice W. M. C. Gummow at Oxford University in 1999 as part of the Clarendon Law Lectures series, sponsored by Oxford University Press. These lectures take up themes of continuity and change in the law, particularly as they appear in the great common law jurisdictions. The tension between continuity and change appears from a consideration of the interaction between statute and the case law which interprets it, of the interaction between equity and statute, and finally of the operation of that constitutional arrangement known as federalism."--BOOK JACKET.
Machine derived contents note: Preface -- Table of Cases -- Lecture 1 The Common Law and Statute -- Lecture 2 Equity Follows the Law -- Lecture 3 Federalism -- Index.
Includes bibliographical references and index.
Keywords: Common law -- England; Statutes -- England; Equity -- England; Federal government -- England; Common law; Equity (Law); Federalism; Constitutional law; Great Britain; Cases (Law); Federal issue; Australia overseas comparisons